Bow hunter syndrome: A rare yet important etiology of posterior circulation stroke. (August 2020) - Qashqari, Hebah; Bhathal, Ishvinder; Pulcine, Elizabeth; Muthusami, Prakash; Moharir, Mahendranath; MacGregor, Daune; Kulkarni, Abhaya; Dlamini, Nomazulu
Highlights: BHS should be suspected in a patient with unexplained vertebral artery dissection. An underlying genetic etiology should be considered in children with BHS. Abstract: A 6-year-old girl presented with acute-onset headache and fluctuating right-sided weakness. Her PedNIHSS was 13. Brain MRI/MRA showed acute pontine arterial ischemic stroke (AIS) and remote right cerebellar and thalamic infarcts. No antecedent trauma or other stroke risk factors were identified. Clinical suspicion of bow hunter syndrome was raised. CT showed congenital C2-C3 fusion and dynamic angiogram confirmed the diagnosis. The management challenges of this rare condition are discussed below.